Farmers or Nomads: Isotopic Evidence of Human–Animal Interactions (770BCE to 221BCE) in Northern Shaanxi, China - Mengjie, Cui; Xue, Shang; Yaowu, Hu; Yan, Ding; Yanfeng, Li; Songmei, Hu (Frontiers in Earth Science, 2022)
Chinese history is composed of the contest, war and admixture between the nomads in the north plateau and the farmers in central China. During the Eastern Zhou Period (770-221 BCE), the nomadic groups such as Rong(戎) and Di(狄), occupied Eurasian Steppes and had frequent contacts with the farmer group in Central China according the historic records. This created a geographic boundary between two groups, named as the agro-pastoral interweaving belt. In order to explore the impact of ethnic integration and human-animal interaction during the Eastern Zhou Dynasty, carbon and nitrogen stable isotope analysis of humans and animals at the Chongpingyuan site, Shaanxi was undertaken. The δ13C (mean: -7.9±0.5‰, n=17) and δ15N values (mean: 8.8±0.6‰, n=17) for human and pigs (mean δ13C: -8.1±0.5‰; mean δ15N:7.5±0.5‰, n=2) revealed that they consumed C4-based foods mainly while the δ13C and δ15N values of cattle (-17.6‰, 4.3‰, n=1), horse (-17.1‰, 4.1‰, n=1) and sheep (mean: -17.4±1.5‰, 6.0±0.8 ‰, n=7) suggest that they relied on C3 plants supplemented with minor C4 plants. Based on the archaeological and historic contexts, we infer that human at Chongpingyuan survived on an agro-pastoral economy with millet agriculture as the economic foundation. Given the isotopic spacing between humans and animals, we found that pigs contributed to the main sources of animal protein whereas other animals might have been provisioned for other purposes such as rituals or properties. In general, no significantly dietary differences between genders and funeral customs are found, but people with abundant burial objects seemed to have consumed more animal protein, possibly related to social heterogeneity.